2012
DOI: 10.1080/02673843.2012.747973
|View full text |Cite
|
Sign up to set email alerts
|

Not just a western girls' problem: eating attitudes among Israeli-Arab adolescent boys and girls

Abstract: The aim of the study was to compare eating attitudes and behaviours between IsraeliArab adolescent boys and girls from two religious, age and residential settings subgroups. The sample consisted of 1966 Israeli-Arab adolescents, from Grades 7-12 (42% boys, 93% Muslims and 7% Christians), who completed the Eating Attitude Test (EAT-26), demographic and clinical questionnaires. The girls had significantly higher EAT-26 scores than boys. Of the students, 17.6% (18.7% of girls and 16.4% of boys) had disturbed eati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 73 publications
3
18
0
Order By: Relevance
“…[23] and Katzman et al [24] also demonstrated predominance of female population suffering from eating disorders. Similar to our findings, earlier studies also reported that there was no association of EAT-26 scores with age [5,21] and BMI [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[23] and Katzman et al [24] also demonstrated predominance of female population suffering from eating disorders. Similar to our findings, earlier studies also reported that there was no association of EAT-26 scores with age [5,21] and BMI [25].…”
Section: Discussionsupporting
confidence: 92%
“…We observed that unhealthy eating attitudes were not just a girls' problem as there was no significant difference in the prevalence of disturbed eating attitudes among both male and female. This finding is comparable to the findings of an earlier study conducted on Israeli-Arab adolescent boys and girls [21]. Tantleff-Dunn et al [22] demonstrated that eating disorders and body image dissatisfaction are becoming normative and universal, not only in females but also in males.…”
Section: Discussionsupporting
confidence: 85%
“…Likewise studies have largely reported the preponderance of body-image disorders and eating disorders among females 3,32,35,43 , to the extent that majority of studies reviewed were conducted solely among females. 7,16,19,26,30,33,34 The participants who were students of the College of Technology tend to have disordered eating attitudes compared to those sampled from the University. In Nigeria, there appears to be some discrimination against undergraduates and graduates of College of Technology in favour of their University counterparts 48 , which may impact negatively on the self-esteem of students in College of Technology.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies of disordered eating attitudes report varying rates including 10% -16% from studies in the Americas 30,31 , 3% -13.7% in Europe 22,32 , 4% -30% in Asia 3,20,23,[33][34][35] . Generally, studies of disordered eating attitudes among males reported rates ranging from 3% -4.5% 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Another Israeli study from 2008 focused on female youth alone and suggested that nearly one third of girls in Israel reported at least two different forms of DE behaviors [18]. Latzer et al [19][20][21], who have studied Arab youth in Israel, revealed a high prevalence of DE among this minority group, and suggested that Christian Arabs had significantly lower DE scores in comparison to Moslem Arabs and Druze. Nevertheless, representative studies comparing rates of DE across Jewish and Arab girls and boys in Israel are still largely unavailable [15,21].…”
Section: Introductionmentioning
confidence: 99%